Level of Adipokines and Insulin Resistance in Obese Javanese Population - Pramudji Hastuti; . Tasmini; AH Sadewa; DM Chornelia; D Karita (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Introduction: Obesity is a condition involving low-level chronic inflammation as indicated by increased levels of C-reactive protein (CRP), TNF, interleukin and other inflammatory markers in the blood. Some endocrine mediators, such as paracrine and autocrine derived from adipose tissue play an important role in regulating the function of adipocytes, especially related to insulin sensitivity. Significant complications of obesity, including insulin resistance as a risk factor of Type 2 diabetes are associated with myocardial infarction, stroke, and peripheral vascular disease.Aim:  The purpose of this study is to determine the level of C-reactive protein (CRP), TNF-alpha, interleukin, resistin and insulin resistance in the obese group compared to controls  sampled from a Javanese population.Method: This study is a preliminary study of 120 people, consisting of 60 obese and 60 controls. Lipid profiles, levels of C-reactive protein (CRP), TNF-alpha, interleukin, resistin were examined with Elisa methods and insulin resistance was calculated by HOMA IR index.Results: This study found levels of glucose, insulin, CRP, and HOMA-IR were higher and significantly different in obese group than control (P <0.05). The TNF-alpha and resistin levels were not significantly different between obese and control groups (P>0.05)Conclusion: The study showed that there were increased levels of adipokines and insulin resistance in obese group compared with the control in the sample of Javanese population.Keywords:  Obese, insulin resistance, CRP, TNF-Alpha, Interleukin, Resistin